Risk group criteria for tailoring adjuvant treatment in patients with endometrial cancer: a validation study of the Gynecologic Oncology Group criteria - Kong, Tae Wook (J Gynecol Oncol, 2015)
OBJECTIVE: The purpose of this study is to validate the Gynecologic Oncology Group (GOG) criteria for adjuvant treatment in a different cohort of patients and to evaluate the simplified risk criteria predicting the prognosis and tailoring adjuvant treatment in patients with surgically staged endometrial cancer. METHODS: We performed a retrospective analysis of 261 consecutive patients with surgically staged endometrial cancer between January 2000 and February 2013. All patients had complete staging procedures and were surgically staged according to the 2009 International Federation of Gynecology and Obstetrics staging system. Clinical and pathologic data were obtained from medical records. We designed the simplified risk criteria for adjuvant treatment according to the risk factors associated with survival. The patients were divided into low and low-intermediate, high-intermediate, and high-risk groups according to the GOG criteria and simplified criteria and their survivals were compared. Receiver-operating characteristic curve analysis was used to evaluate the prognostic significance of both criteria. RESULTS: Median follow-up time was 48 months (range, 10 to 122 months). According to the GOG criteria, we identified 197 low and low-intermediate risk patients, 20 high-intermediate risk patients, and 44 high-risk patients. There were significant differences in disease-free (p<0.001) and overall survival (p<0.001) among the three groups. Using the simplified risk criteria, we identified 189 low and low-intermediate risk patients, 28 high-intermediate risk patients, and 44 high-risk patients. There were significant differences in disease-free (p<0.001) and overall survival (p<0.001) among the three groups. The performance of the simplified criteria (area under the curve [AUC]=0.829 and 0.916 for disease recurrences and deaths, respectively) was as good as the GOG criteria (AUC=0.836 and 0.921 for disease recurrences and deaths, respectively). CONCLUSION: The simplified criteria may be easily applicable and offer useful information for planning strategy of adjuvant treatment in patients with surgically staged endometrial cancer as the GOG criteria.